2011
DOI: 10.1007/s11294-011-9292-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Euro on Sectoral Equity Returns and Portfolio Risk

Abstract: Diversification, Volatility spillover, GARCH-M, G11, C22, C01,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Second, the liberalization of capital markets in Europe has had an effect, and portfolio compositions are becoming more similar. Reduction in barriers to capital mobility with exchange rates no longer barriers to equity trading in the Euro area, a number of empirical research studies have found increased correlation among the performance of national stock markets and an overall increase in the degree of co-movement between European equity markets upon the introduction of the single currency (Asal, 2011;Cappiello et al, 2010 andAdjaouté andDanthine, 2004). As a result, portfolios have begun to be allocated along pan-European sectoral lines rather than on a country basis.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the liberalization of capital markets in Europe has had an effect, and portfolio compositions are becoming more similar. Reduction in barriers to capital mobility with exchange rates no longer barriers to equity trading in the Euro area, a number of empirical research studies have found increased correlation among the performance of national stock markets and an overall increase in the degree of co-movement between European equity markets upon the introduction of the single currency (Asal, 2011;Cappiello et al, 2010 andAdjaouté andDanthine, 2004). As a result, portfolios have begun to be allocated along pan-European sectoral lines rather than on a country basis.…”
Section: Introductionmentioning
confidence: 99%